Annexin‐A1 deficiency exacerbates pathological remodelling of the mesenteric vasculature in insulin‐resistant, but not insulin‐deficient, mice. (11th February 2020) - Jelinic, Maria; Kahlberg, Nicola; Leo, Chen Huei; Ng, Hooi Hooi; Rosli, Sarah; Deo, Minh; Li, Mandy; Finlayson, Siobhan; Walsh, Jesse; Parry, Laura J.; Ritchie, Rebecca H.; Qin, Cheng Xue
Abstract : Background and purpose: Arterial stiffness, a characteristic feature of diabetes, increases the risk of cardiovascular complications. Potential mechanisms that promote arterial stiffness in diabetes include oxidative stress, glycation and inflammation. The anti‐inflammatory protein annexin‐A1 has cardioprotective properties, particularly in the context of ischaemia. However, the role of endogenous annexin‐A1 in the vasculature in both normal physiology and pathophysiology remains largely unknown. Hence, this study investigated the role of endogenous annexin‐A1 in diabetes‐induced remodelling of mouse mesenteric vasculature. Experimental approach: Insulin‐resistance was induced in male mice ( AnxA1 +/+ and AnxA1 ‐/‐ ) with the combination of streptozotocin (55mg/kg i.p. x 3 days) with high fat diet (42% energy from fat) or citrate vehicle with normal chow diet (20‐weeks). Insulin‐deficiency was induced in a separate cohort of mice using a higher total streptozocin dose (55mg/kg i.p. x 5 days) on chow diet (16‐weeks). At study endpoint, mesenteric artery passive mechanics were assessed by pressure myography. Key results: Insulin‐resistance induced significant outward remodelling but had no impact on passive stiffness. Interestingly, vascular stiffness was significantly increased in AnxA1 ‐/‐ mice when subjected to insulin‐resistance. In contrast, insulin‐deficiency induced outward remodelling and increased volume compliance in mesenteric arteries, regardless of genotype. In addition, the annexin‐A1 / formyl peptide receptor axis is upregulated in both insulin‐resistant and insulin‐deficient mice. Conclusion and implications: Our study provided the first evidence that endogenous AnxA1 may play an important vasoprotective role in the context of insulin‐resistance. AnxA1‐based therapies may provide additional benefits over traditional anti‐inflammatory strategies for reducing vascular injury in diabetes. Abstract :